Adição de nanopartículas de Ti em matriz de Fe através da deposição por magnetron sputtering - Ferreira, Narayanna Marques (2011)
Microalloyed steels constitute a specific class of steel with low amount of carbon and microalloying elements such as Vanadium (V), Niobium (Nb) and Titanium (Ti). The development and application of microalloyed steels and steels in general are limited to the handling of powders with particles of submicron or nanometer dimensions. Therefore, this work presents an alternative in order to construction of microalloyed steels utilizing the deposition by magnetron sputtering technique as a microalloying element addiction in which Ti nanoparticles are dispersed in an iron matrix. The advantage of that technique in relation to the conventional metallurgical processes is the possibility of uniformly disperse the microalloying elements in the iron matrix. It was carried out deposition of Ti onto Fe powder in high CH4, H2, Ar plasma atmosphere, with two deposition times. After the deposition, the iron powder with nanoparticles of Ti dispersed distributed, were compacted and sintered at 1120 ° C in resistive furnace. Characterization techniques utilized in the samples of powder before and after deposition of Ti were Granulometry, Scanning Electron Microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX) and X-ray diffraction (DRX). In the case of sintered samples, it was carried out characterization by SEM and Vickers Microhardness assays. The results show which the deposition technique by magnetron sputtering is practicable in the dispersion of particles in iron matrix. The EDX microanalysis detected higher percentages of Ti when the deposition were carried out with the inert gas and when the deposition process was carried out with reactive gas. The presence of titanium in iron matrix was also evidenced by the results of X-ray diffraction peaks that showed shifts in the network matrix. Given these results it can be said that the technique of magnetron sputtering deposition is feasible in the dispersion of nanoparticles of iron matrix in Ti.